Religiosity in the Coping Mechanisms of Bullied Students: A Case Report - Nabila, Nabila; Yandri, Hengki (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2024)
The problem of bullying in the school environment is becoming an increasingly worrying issue. Victims of bullying often experience significant psychological impacts, including decreased self-esteem, anxiety and depression which impact their religiosity. This research aims to describe in depth the condition of religiosity of students who are victims of bullying in overcoming the psychological impacts caused by bullying. Through a case report approach, this research describes the experience of a student with the initials SM who was a victim of bullying and how he used his religious beliefs to deal with this situation through semi-structured interviews, data collected using thematic analysis. The research results show that religiosity can be a source of strength, hope and meaning for victims of bullying. These findings provide important implications for educators, counselors, and parents in developing more holistic interventions to help victims of bullying.